Suspected primary photosensitisation in cattle grazing red clover (Trifolium pratense) - Tettamanti, Agustina; Livio, Juan; Micheloud, Juan Francisco; Livio, Rubén; Poo, Juan Ignacio; Lauro, Adriana Araceli; Scioli, Maria Valeria; Canton, German Jose; Garcia, Juan Agustin (Taylor and Francis, 2025)
Case history: In April and June of 2024, two outbreaks of photosensitisation occurred in a herd of 354 beef cows and calves in Buenos Aires province, Argentina. Both outbreaks occurred in the same paddock, where red clover (Trifolium pratense) was the dominant pasture species, combined with tall fescue (Schedonorus arundinaceus, previously Festuca arundinacea), white clover (T. repens), bird’s foot trefoil (Lotus corniculatus), and perennial ryegrass (Lolium perenne). Clinical findings : Signs of head tilt, restlessness, tail swishing, and searching behaviour for shade and water were first observed 15–19 days after grazing, with skin necrosis and eyelid inflammation visible on closer examination. A cumulative incidence of 5.6% and 10.7% was recorded in each outbreak with all animals recovering 5–10 days after removal to a paddock composed of wheatgrass (Triticum aestivum) and Festuca spp. Laboratory and pathological: Following the second outbreak, nine serum samples and seven ear skin biopsies were collected from affected animals for assessment of hepatic enzyme activities and histopathology, along with a pasture sample to assess the spore count for Pithomyces chartarum. Serum activity levels of glutamic oxaloacetic transaminase (GOT) and gamma-glutamyl transferase (GGT) were normal in nine and four affected cows, with slightly elevated GGT activities in the remaining five cows. Activities of all other liver enzymes were within normal limits and there was no sign of icterus. Histological examination of the ear skin biopsies revealed necrotising dermatitis and epidermal hyperplasia compatible with photosensitisation. The spore count for P. chartarum was low (11,250 spores/g fresh pasture). Diagnosis: The epidemiological data, clinical presentation and clinical-pathology findings suggest that these cows were affected by primary photosensitisation most probably due to the ingestion of T. pratense. Clinical relevance: Identifying a plant species as a cause of primary photosensitisation is difficult, and the aetiological agent often remains unidentified. The association between consumption of a sward containing T. pratense and the photosensitisation reported in this study suggests that this plant species may be acting as a primary cause of photosensitisation in cattle. This study highlights the need for further research to identify toxic elements in T. pratense and their effects on livestock.